Phenotypic variation of the population of Anopheles (K.) neivai (Diptera: Culicidae) in the pacific coast of Colombia (Colombia Medica, 1987)
Between the years 1984 and 1985, larvae and adult mosquitoes of Anopheles (Kerteszia) were collected in different localities of the Pacific coast of Colombia: El Trueno, Concherito, and Santa Cruz in the Naya River basin, Juanchaco y Ladrilleros in the Valle del Cauca Department and Charambirá in the Chocó Department. Preliminary surveys indicated the presence of two species: A. neivai and A. homunculus. Due to some doubts originating from the existence of notable morphological differences in the specimens studied, more detailed observations were done, and the conclusion was the existence of a single species, A. neivai, with significant phenotypical variations, which create some taxonomical and probably epidemiological problems.